THE FORMATION OF INFORMATION SECURITY CULTURE IN SOCIETY: CURRENT CHALLENGES AND PROSPECTS (FEATURES AND PROBLEMS OF IMPLEMENTING ECONOMIC REFORMS IN AZERBAIJAN, 2025)
The article explores the role of information security culture in modern society and its formation. Information security is no longer limited to technical measures but also covers social, legal, and economic aspects. The rapid development of digital technologies and the widespread use of the internet have made the protection of personal and corporate data increasingly relevant. The article emphasizes that public awareness, improvement of legal frameworks, and development of technological infrastructure are key factors in shaping information security culture. In today’s world, cyber threats create serious risks on both individual and collective levels. During the COVID-19 pandemic, the rise of remote work caused phishing and malware attacks to increase, raising the risk of personal data leaks. In Azerbaijan, joint initiatives by the state and private sector have strengthened the national cybersecurity ecosystem. At the same time, the experiences of countries such as “e-Estonia” and Japan show that information security can be reinforced not only by technical means but also through education, awareness, and social approaches. The article reviews international practices and measures taken in Azerbaijan, including national strategies, a stronger legal base, “Smart City” and “Smart Village” projects, cybersecurity training, and preventive technological solutions. Recommendations include expanding awareness campaigns, strengthening legal and governance mechanisms, enhancing public-private cooperation, and applying AI-based innovative cyber defense systems. Ultimately, the article stresses that developing information security culture depends not only on technology but also on the knowledge and responsible behavior of every member of society, ensuring the protection of both national and individual interests.
Keywords: information security, digital literacy, cooperation, cyber culture, education